Organizational Agility and Social Capital as Drivers of Resilience in the touristic SMEs: A Dynamic Capabilities Perspective - AHACHMI , Mustapha; LAHFIDI , Abdelhaq (Revue Internationale des Sciences de Gestion, 2025)
Organizational resilience is a growing concern in volatile sectors like tourism, especially in the wake of global crises such as COVID-19. While scholarly interest has increased, the influence of intangible resources on resilience in SMEs from emerging economies remains underexplored. This study examines how organizational agility and social capital shape the resilience of Moroccan tourism SMEs, focusing on the mediating role of dynamic capabilities. Anchored in the Dynamic Capabilities View and the Resource-Based View, the research uses PLS-SEM on data from 254 restaurant-sector SMEs in the Marrakech-Safi region. Findings reveal that agility boosts both social capital and resilience, with dynamic capabilities serving as mediators. Independent restaurants show greater adaptability. The study contributes to resilience theory in emerging contexts and offers practical guidance for SME managers.